The Influence of Service, Price, Location, Promotion, and Trust on Patient Decisions to Conduct Examinations at the Solo City Clinical Laboratory - Udiani, Asih Arifah; Isa, Muzakar; Romadhon, Yusuf Alam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study evaluates the effects of service quality, pricing, location, and promotion on decision-making regarding taking laboratory examinations in a clinical lab clinic in Solo City. Given the rapid pace of development in both technology science and healthcare needs, these factors must be understood to improve the competitiveness and performance of clinical laboratories. SEM data was collected from 100 respondents who were examined at the Solo City Clinical Laboratory using Smart PLS software. The results support the hypothesis that service quality, pricing, and promotion have a significant impact on patient trust, influencing their brand decision-making process. But on trust and judgment, that doesn't appear to be a factor. This study underscores the need for a holistic approach to patient engagement, recognizing the interrelated nature of these elements in constructing trust and decisions. Our study does offer rich perspectives that can help clinical laboratories develop best practices, especially in resource-limited settings that would Strive to provide universal access to high-quality diagnostic services. Generalization to other healthcare contexts and longitudinal studies of the relationships with patient loyalty/retention are warranted in future research.